Women's leadership and SMEs' CSR performance: Family versus nonfamily firms - Nhat Minh Tran; Thanh Huyen Nguyen (Cogent Business & Management, 2022)
The purpose of this study is first to examine the impact of family control on SMEs' corporate social responsibility (CSR) performance and, second, investigate how the proportion of female managers in the top management team (TMT) is related to CSR performance in family versus nonfamily SMEs. To answer these questions, we use panel data of manufacturing SMEs from the database of UNU-WIDER over a period from 2011 to 2015 and run fixed effect regressions. Our findings indicate that first, nonfamily SMEs outperform family ones in terms of CSR performance; second, similar to the previous idea, we find a significant and positive relationship between the increasing presence of female managers in the TMT and CSR practices. However, we also find that this positive relationship only occurs with nonfamily SMEs and not with family SMEs. This paper focuses specifically on Vietnamese SMEs and CSR performance. It tests the impact of family ownership on this relationship, as well as the moderating effect of this ownership on the role of female managers in promoting CSR performance.
Keywords: M14; 650; Vietnam; CSR performance; family SMEs; female manager; nonfamily SMEs